(untitled) (World Science, 2023)
The study selected a technical solution to improve the quality of rubber products in rolls with roller modernization based on the addition of grooves. The essence of roller modernization is that the second of each pair of ring sections of rolls is equipped with small grooves, as well as the ring sections of each roll are made on removable ring sectors fixed on it. Such a proposed upgrade of rollers will help improve the quality of manufactured rubber products by rollers.